2014
DOI: 10.1093/ije/dyu043
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in alcohol-attributable mortality compared with all-cause mortality: a systematic review and meta-analysis

Abstract: Alcohol was identified as a factor underlying higher mortality risks in more disadvantaged populations. All alcohol-attributable mortality is in principle avoidable, and future alcohol policies must take into consideration any differential effect on socioeconomic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
168
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 94 publications
17
168
2
3
Order By: Relevance
“…Some papers found high educational level and/or income associated with risk consumption 12,15,26 , while others have found a higher rate of drinkers among subjects with lower educational level 13,27,28 or did not even find a relation 9,14 . Nevertheless, there is strong evidence that people with lower socioeconomic level are more susceptible to suffering consequences regarding the use of alcohol 29 . Therefore, with the aim of decreasing health inequalities, strategies to control and prevent the heavy use of alcohol in this group are extremely important, because these subjects present a higher concentration of other health risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers found high educational level and/or income associated with risk consumption 12,15,26 , while others have found a higher rate of drinkers among subjects with lower educational level 13,27,28 or did not even find a relation 9,14 . Nevertheless, there is strong evidence that people with lower socioeconomic level are more susceptible to suffering consequences regarding the use of alcohol 29 . Therefore, with the aim of decreasing health inequalities, strategies to control and prevent the heavy use of alcohol in this group are extremely important, because these subjects present a higher concentration of other health risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of population data for alcohol use and harm in different socioeconomic groups have noted consistently that the same patterns of alcohol consumption cause more harm in drinkers of lower than higher socioeconomic status. 3 Reasons for the relation between drinking patterns, health, and socioeconomic status are debated. The major candidate explanations are: that drinkers of lower socioeconomic status engage in riskier drinking patterns than do those of higher socioeconomic status; that the relation is confounded by variations between drinkers of different socioeconomic status with respect to the prevalence of other risk factors (eg, obesity and smoking); and that heavy drinkers who have greater alcohol-related harm undergo downward social mobility.…”
Section: Socioeconomic Status and Susceptibility To Alcohol-related Harmmentioning
confidence: 99%
“…All alcohol-attributable harms are in principle avoidable (Rehm et al, 2006;Probst et al, 2014). The primary objective of the introduction of a MUP is to reduce alcohol-attributable harms.…”
Section: Implications For Minimum Unit Pricing As a Policy In Irelandmentioning
confidence: 99%
“…In 2008 an average of 88 alcohol-related deaths were recorded every month in Ireland (Lyons et al, 2011). Recent international studies have repeatedly shown that alcoholattributable mortality is higher in lower socioeconomic groups (Harrison and Gardiner, 1999;Metcalfe et al, 2005;Probst et al, 2014;Mackenbach et al, 2015). For example, a recent metaanalysis of data from 14 countries showed, depending on the measure of socioeconomic status, a F o r P e e r R e v i e w 4 three to ten-fold increase in alcohol-attributable deaths in men with a lower socioeconomic status (Probst et al, 2015).…”
Section: Introductionmentioning
confidence: 99%